Innovative Strategies for Urban Waste Management: Integration of Technology and Community Participation - Lasaiba, Mohammad Amin; Lasaiba, Irvan (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
Urban waste management is unavoidable in efforts to maintain and improve the quality of life in cities worldwide. This research examines various aspects of urban waste management by adopting a literature review methodology. In the context of urban waste management, it is not just a local issue but also significantly impacts the environment, public health, and future cities' sustainability. The study's findings indicate that urban waste management is a critical and complex issue many cities face globally. The challenges involved require sustainable solutions to ensure the future sustainability of cities. One crucial step in addressing these challenges is raising public awareness about the importance of proper waste management. The public can better understand and appreciate sustainable waste management practices such as segregation, recycling, and waste reduction through appropriate education and campaigns. By developing the necessary infrastructure and implementing innovative solutions, cities can reduce the negative impacts of waste management.